The Role of Teachers in Cultivating Communicative Values in Schools - Ujang Jamaludin; Ikman Nur Rahman; Rosdiana Putri (Jurnal Ilmiah Sekolah Dasar, 2021)
The use of polite language is very low used by elementary school students, causing misunderstanding or miscommunication in learning. This study aims to analyze the process of cultivating character to increase students' communicative character value in the learning process. The research method used in this research is a qualitative method, with a descriptive qualitative type. This research was conducted with the research subjects of teachers and students of fourth grade. The object of this research is the role of the teacher in instilling students' communicative character values. The data collection techniques used were observation, interview, and documentation techniques. The results of this study revealed that the teacher's way of carrying out the inculcation of communicative character values in grade fourth went well. The inculcation of communicative character values has a good impact on the communicative character of students. The implication of this research has the impact of cultivating character values that can create a more active atmosphere in the classroom. Students can work together with one another, and the student's communication skills are improved